Duisburg and its port, endpoint of China's silk road: Opportunities and risks - Werner Pascha (OrdnungsPolitisches Portal (OPO), 2021)
The question to what extent the EU, Germany, its regional states or individual localities can and should cooperate with China has gained considerable importance recently. This paper discusses the city of Duisburg, an important logistics hub in western Germany, next to the rivers Rhine and Ruhr, as a particularly interesting case study. Its location is ideal as the "western terminus" for the rail services of the "new silk road", but the precarious economic situation as a former city of steel and coal make Duisburg particularly vulnerable to economic and political risks. The paper identifies relevant pro and con factors and evaluates the available evidence. The economic heritage and current situation of Duisburg are indeed challenging. Duisburg has noticeably profited from the Chinese interest in its logistics network, but the impetus is not significant enough for the city to fully recover from the decline of coal and steel industries. A large share of the potential benefits has probably already been realized, while current plans to increase the container capacity of the port further should be duly acknowledged. Positive linkage effects with other industries, beyond rail and logistics, still seem rather limited. With respect to the political dimension, the typical risks for local communities often associated with the Belt and Road Initiative were somewhat limited in Duisburg's case, because Duisburg, as a part of Germany, is not in a particularly dire situation and as Duisburg's port activities are profitable even without the China business, so the potential leverage of Chinese actors is limited, and because Duisburg is not the home of many high-tech companies that might be attractive targets. In the case of the Duisburg-Huawei cooperation, which does indeed hold some political risks, the momentum has declined recently, due to the various checks and balances that are in place, while the win-win projects of the agenda will hopefully still be realized. Both the idea of an economic bonanza beckoning on the horizon and the concern about looming political risks seem to have been exaggerated. Currently, the city seems to be in a phase of reconsidering its future options and possible trajectories with respect to China.
Keywords: 330; Duisburg; China; New silk road; Belt and Road Initiative; regional economic development